In search of a winning candidate profile: an application of conjoint analysis - Cárdenas Bonilla, Édgar (2009)
This study uses conjoint analysis, a multivariate statistical technique of categorical explanatory variables to examine the decision structure used by the voter at the time of casting his vote. The methodology allowed us to establish the attributes that Peruvian voters consider favorable when selecting a candidate.